Implementing Discipline for Early Childhood: Strategies and Teacher Roles - Destiana, Evie; Anggraeni, Yuni; Fatmala, Endang; Wulandari, Andini (Universitas Muhammadiyah Sidoarjo, 2024)
Discipline is one of the characters that needs to be applied from an early age, especially by parents. The fact is that there are still many parents who do not understand and are moved to apply disciplinary behavior to their children. The purpose of this study is to analyze the role of teachers in optimizing the development of discipline application from early childhood. This research uses a qualitative approach with the type of research used, namely descriptive qualitative research. Data collection was carried out using interview, observation and documentation methods. Sources of research data are the principal, 1 assistant teacher or companion teacher 2 and 68 students. The researcher is the core instrument in the research and uses supporting instruments in the form of interview guidelines, observation guidelines. The analysis technique used is descriptive analysis from Miles & Huberman using an interactive model. The results showed that the teacher's role in children's discipline is as a good role model for children, teachers as educators and mentors by introducing and familiarizing children with discipline in everyday life, and teachers as evaluators. The teacher's efforts in implementing discipline are exemplary, habituation, and using reward and punishment methods. Factors that hinder teachers in implementing children's disciplinary attitudes are external factors, namely family, community environment, internal factors of hyperactive or tantrum children's attitudes. The supporting factor is the role of parents who are willing to cooperate well in developing their children's disciplinary attitudes. It can be concluded that teachers have an important role in shaping student discipline at school.